GAMBARAN DETERMINAN KEJADIAN STUNTING PADA BALITA DI DESA MELAYA - Ni Putu Vina Ratnyani; Ni Ketut Ayu Mirayanti; Ni Made Nopita Wati (Rena Cipta Mandiri, 2026)
Stunting is a chronic nutritional problem in toddlers that remains a major concern, especially in developing countries. This condition is caused by long-term malnutrition and impacts linear growth disorders, increased risk of illness, and impaired cognitive and motor development in children. Determinants of stunting include a history of low birth weight (LBW), a history of toddler nutritional intake, maternal nutritional intake during pregnancy, and family clean and healthy living behaviors (PHBS). This study aims to determine the determinants of stunting in toddlers in Melaya Village. This study used a quantitative descriptive design with a cross-sectional approach. Respondents numbered 85 toddlers selected using probability sampling techniques. Data were collected using a questionnaire and analyzed univariately. The results showed that most toddlers did not have a history of LBW (91.8%), the history of toddler nutritional intake was in the adequate category (69.4%), maternal nutritional intake during pregnancy was mostly in the ≤8 category (81.2%), and family PHBS was mostly in the good category (63.5%). These findings indicate that fulfilling nutrition from pregnancy to toddlerhood and the implementation of family PHBS play an important role in supporting toddler growth. The conclusion of the study shows that the determinants of stunting incidence in toddlers in Melaya Village are mostly in the sufficient to good category, so that it can be a basis for efforts to prevent stunting through improving nutrition and healthy family lifestyles.